2006
DOI: 10.1093/humrep/del288
|View full text |Cite
|
Sign up to set email alerts
|

First IVF treatment—short-term impact on psychological well-being and the marital relationship

Abstract: Couples undergoing their first IVF treatment are as a group well adjusted and manage to handle the short-term emotional strain under treatment. The determining factor for short-term emotional response of treatment was whether pregnancy was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 28 publications
4
71
0
8
Order By: Relevance
“…However, a study that examined the depressed mood of men 2-4 weeks prior to treatment showed that they were less depressed than other men, indicated by the higher mean scores in subscale of PGWB (m = 16.3 vs. 15.8) [6].…”
Section: Depressionmentioning
confidence: 98%
See 3 more Smart Citations
“…However, a study that examined the depressed mood of men 2-4 weeks prior to treatment showed that they were less depressed than other men, indicated by the higher mean scores in subscale of PGWB (m = 16.3 vs. 15.8) [6].…”
Section: Depressionmentioning
confidence: 98%
“…A study that analyzed the pretreatment data after the results of the pregnancy test had been disclosed did not identify significant differences in depression levels between women who finally succeeded in conceiving and those who failed [22]. However, one of the seven studies found no significant difference in depression scores between infertile and normal women (subscale of PGWB, m = 15.4 vs. 15.3) [6], with the measurement point at 2-4 weeks before treatment. Contradictory findings were presented in a study conducted in the USA, indicating that incidences of major depressive disorders (MDD) and other depressive disorders (ODD) among IVF women were lower than among the primary care population (PHQ-9, MDD, 1 % vs. 10 %; ODD, 2 % vs. 6 %) [21], where the PHQ instruments were first developed and published [25].…”
Section: Depressionmentioning
confidence: 98%
See 2 more Smart Citations
“…Findings document that in general women reported higher emotional difficulties than men in almost every stages of infertility (Holter, Anderheim, Bergh, & Moller, 2006; Markestad et al ., 1998), although patterns of reactions along the infertility experience are similar (Boivin et al ., 1998). When examining gender differences on the importance attributed to parenthood, no differences have been found (Moura‐Ramos, Gameiro, Canavarro, Soares, & Santos, 2012).…”
Section: Introductionmentioning
confidence: 97%